Environmental and Nutritional Chemistry of Wild Harvested Blueberries vs. Commercial Blueberries: Depositional and Uptake Chemistry and Human Health Assessment - Maynard, Christy Ann Marie (Université d'Ottawa / University of Ottawa, 2023)
In northern Saskatchewan, Canada, there are several active and decommissioned uranium mines and mills licensed by Canada's nuclear regulator, the Canadian Nuclear Safety Commission (CNSC). In these areas, Indigenous communities harvest traditional foods and Canadian diet studies have identified wild berries as an important part of their diet (Furgal, Powell, & Myers, 2005), (Roseanne C. Schuster, 2011), (Health Canada, 2010). Food ingestion is recognized as an exposure pathway of anthropogenic and naturally occurring radioactive materials and trace metals (Kuhnlein & Chan, 2000) and some communities may be concerned their traditional foods are contaminated from facility operations. Wild blueberries and the soil the plant roots grew in were sampled approximately 10-25 kms away from CNSC-licensed facilities in northern Saskatchewan. As a comparison, commercially-available blueberries and soil were collected from Ontario farms and blueberries were obtained from grocery stores. Samples were analyzed for trace elemental concentrations by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and radionuclide activity concentrations were measured. Annual ingestion dose for blueberry consumption was conservatively estimated to be 0.0079 mSv/a. The blueberry results were compared to international guidelines and published literature and were not found to pose an ingestion health risk. The activity concentrations in blueberries ranged between 0.001-0.006 Bq/g d.w. for ²¹⁰Po and 0.003-0.005 Bq/g d.w. for ²¹⁰Pb and the concentrations of cadmium and arsenic in blueberries ranged between 0.002-0.07 μg/g and 0.0002-0.007 μg/g, respectively. This research project identifies geochemical relationships between radionuclides and trace elements in blueberries, examines the uptake chemistry, environmental cycling of radionuclides and trace elements, and the soil mineralogy and composition, helps inform CNSC's regulatory decision-making process, and supports future human health risk communication with Indigenous communities.
Keywords: Wild Blueberries; Radionuclides; Trace Elements; Ingestion Dose; Atmospheric Deposition; Soil Uptake Chemistry; Traditional food; Indigenous; COPC; NORM; Chemical analogue